Inflammatory evidence for the psychosis continuum model. (May 2016) - Mørch, Ragni H.; Dieset, Ingrid; Færden, Ann; Hope, Sigrun; Aas, Monica; Nerhus, Mari; Gardsjord, Erlend S.; Joa, Inge; Morken, Gunnar; Agartz, Ingrid; Aukrust, Pål; Djurovic, Srdjan; et al.
Highlights: Inflammatory markers, cytokines are implicated in pathophysiology of severe mental disorders. We measured levels of inflammatory markers in patients ( n  = 992) and healthy controls ( n  = 638). Levels of sTNF-R1 and IL-1Ra were increased in patients compared to controls. The schizophrenia group showed higher levels than the affective group providing evidence for the psychosis continuum model. Antipsychotic medication was not associated with the inflammatory markers. Abstract: Background: Inflammation and immune activation have been implicated in the pathophysiology of severe mental disorders. Previous studies of inflammatory markers, however, have been limited with somewhat inconsistent results. Aims: We aimed to determine the effect sizes of inflammatory marker alterations across diagnostic groups of the psychosis continuum and investigate association to antipsychotic medications. Methods: Plasma levels of soluble tumor necrosis factor receptor 1 (sTNF-R1), interleukin 1 receptor antagonist (IL-1Ra), osteoprotegerin (OPG), and von Willebrand factor (vWf) were measured in patients ( n  = 992) with schizophrenia spectrum (SCZ, n  = 584), schizoaffective disorder (SA, n  = 93), affective spectrum disorders (AFF, n  = 315), and healthy controls (HC, n  = 638). Results: Levels of sTNF-R1 ( p  = 1.8 × 10 −8, d   =  0.23) and IL-1Ra ( p  = 0.002, d   =  0.16) were increased in patients compared to HC. The SCZ group had higher levels of sTNF-R1 ( p  = 8.5 × 10 −8, d   =  0.27) and IL-1Ra ( p  = 5.9 × 10 −5, d  = 0.25) compared to HC, and for sTNF-R1 this was also seen in the SA group ( p  = 0.01, d   =  0.3) and in the AFF group ( p  = 0.002, d   =  0.12). Further, IL-1Ra ( p  = 0.004, d   =  0.25) and vWf ( p  = 0.02, d  = 0.21) were increased in the SCZ compared to the AFF group. There was no significant association between inflammatory markers and use of antipsychotic medication. Conclusion: We demonstrate a small increase in sTNF-R1 and IL-1Ra in patients with severe mental disorders supporting a role of inflammatory mechanisms in disease pathophysiology. The increase was more pronounced in SCZ compared to AFF supporting a continuum psychosis model related to immune factors.